Stroke Seasonality and Weather Association in a Middle East Country: A Single Tertiary Center Experience - Alghamdi, Saeed A. M.; Aldriweesh, Mohammed A.; Al Bdah, Bayan A.; Alhasson, Muath A.; Alsaif, Sultan A.; Alluhidan, Waleed A.; Almutairi, Faisal M.; Alskaini, Mohammed A.; Alotaibi, Naser; Al Khathaami, Ali M. (Frontiers in Neurology, 2021)
Background Stroke is a medical condition that leads to major disability and mortality worldwide. Some evidence suggests that weather and seasonal variations could have an impact on stroke incidence and outcome. However, the current evidence is inconclusive. Therefore, this study examines the seasonal variations and meteorological influences on stroke incidence and outcome in the largest city in Saudi Arabia. Methods From February 2016 until July 2019, we retrospectively reviewed data from all patients admitted to the stroke unit in tertiary academic center in Saudi Arabia with acute ischemic (AIS) or hemorrhagic stroke (HS). The corresponding daily meteorological data were obtained for the same period. We considered the months from November to March as the cold season and April to October as the hot season. Results The final cohort included 1,271 stroke patients; 60.89% (n=774) cases occurred in the hot season, while 39.1% (n=497) in the cold season. Males accounted for 69.6% (n=884) of the cases. The proportion of ischemic stroke was 83.2% (hot season 83.9% [n=649] vs. cold season 82.3% [(n=409]). We found no statistically significant difference between seasons (hot or cold) in stroke incidence, severity (NIHSS), hospital course (pneumonia, thromboembolism, intensive care stay, or length of stay), or outcome (mRS on discharge and death). Conclusions In Riyadh, Saudi Arabia, our study found no impact of weather or seasonal variations on stroke incidence, hospital course, or outcomes. However, our findings warrant further research in different country regions.